Answer:
y=-x-2
Step-by-step explanation:
To find the slope of the line, you can use the slope formula. I did this with (-3,1) and (2,-4) to get: (1+4)/(-3-2). This ends up as -5/5, which simplifies to -1.
next I plugged in the slope and one point into the line equation: y=mx+b. I plugged in (-4)=(-1)(2)+b. This equated to b=-2.
Check Work:
The equation -4=(-1)(2)-2 is true
The equation 1=(-1)(-3)-2 is true
Let's say that the unknown value here is c. Although we are given two points on the line, it is only necessary to use one as there is only one unknown value, so let's say we choose the point (6, -12) and substitute this into the equation:
-12 = 1(6) - c
-12 - 6 = -c
-18 = -c
c = 18
Thus the equation for the line is y = 1x - 18
X = -2
3 x -2 = -6
-6 -2= -8
|-8| = 8
-2 + 1= -1
|-1|=1
Lets see!
We need to use the pythagorean theorem (a^2+b^2=c^2) to check.
So..
15^2+ 17^2 = 19^2
225+ 289= 361
Hm 225 and 289 do NOT equal 361 therefore it is NOT a right triangle.